Non-destructive evaluation in high strength concrete using ultrasonic pulse echo - Sivasubramanian, K.; Ramanjaneyulu, K.; Jaya, K.P.; Neelemegam, M. (Journal of Structural Engineering, 2024)
Non-destructive testing of concrete specimens has been an area of focussed research for many years. There has been an increased use of ultrasonic techniques for non-destructive testing in civil engineering as well as in other engineering disciplines. The present work focuses on identifying defects (like honeycomb and voids) and hollow pipe placed at different depths in high strength concrete specimens. The present work uses ultrasonic pulse echo (UPE) method to detect the defects. Specimens have been cast and the data collected using UPE method. The results of the investigation show that the UPE can be used to identify and locate defects at depths from 50mm to 200mm.